(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Adolescence is a period of child development towards the adult phase where emotional behavior is still changing and a period of self-discovery. At this time adolescents must be able to control emotions and get good parenting support. The purpose of the study was to explain empirically and theoretically the relationship between toxic parenting and the emotional behavior of adolescents in class XI at SMAN 1 Merapi Barat. Researchers used quantitative methods with simple random sampling techniques with a sample population of 119 with an age range of 16-18 years. Data analysis was carried out using statistical tests, the measuring instruments used were the emotional behavior scale and the toxic parenting scale. The results showed that there is a very significant relationship between toxic parenting and emotional behavior of adolescent children with a correlation value of R = 0.759 with a Rsquare value = 0.576 P = 0.000 (P < 0.01). The amount of effective contribution given by the toxic parenting variable to emotional behavior is R2 = 0.576 (57.6%). So there are still 42.4% of the influence of other factors related to emotional behavior.